HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG IMUNISASI DPT PADA BAYI DENGAN PERILAKU PENCEGAHAN PENYAKIT DIFTERI PERTUSIS DAN TETANUS DI PUSKESMAS KORPRI BANDAR LAMPUNG TAHUN 2020 - Ringgo Alfarisi; Jordy Oktobiannobel; Tri Wibowo Julianto (PSIKOLOGI KONSELING, 2021)
DPT immunization is the basic immunization used to prevent diphtheria pertussis and tetanus. According to data from the Bandar Lampung City Health Office from 30 health centers in Bandar Lampung, the Korpri Puskesmas in Sukarame District is the health center with the lowest complete basic immunization coverage, which is 60.8% in 2015. The low immunization coverage rate is inseparable from health behavior and parental knowledge about DPT immunization. Purpose of this study to determine the relationship between the level of mother's knowledge about DPT immunization in infants with the prevention behavior of diphtheria pertussis and tetanus at the Korpri Puskesmas Bandar Lampung in 2020. This study used an observational and analytic type of study with a cross sectional approach and a questionnaire interview method. The sample used in this study were mothers who had babies in the work area of the Korpri Bandar Lampung Community Health Center in 2020. Data analysis used Chi-Square. The result It is known that 7 mothers (77.8%) have bad knowledge about DPT immunization and bad behavior towards DPT disease prevention, as many as 2 mothers (22.2%) have bad knowledge about DPT immunization and good behavior towards DPT disease prevention. A total of 28 mothers (33.3%) had good knowledge about DPT immunization and bad behavior towards DPT disease prevention, as many as 56 mothers (66.7%) had good knowledge about DPT immunization and good behavior towards DPT disease prevention. Chi-square test results obtained p-value = 0.024 (p ≤ 0.05), which means that there is a relationship between the level of maternal knowledge and the prevention behavior of diphtheria, pertussis and tetanus. There is a significant relationship between the level of maternal knowledge about DPT immunization in infants with the prevention behavior of diphtheria pertussis and tetanus at the Korpri Puskesmas Bandar Lampung in 2020 with a p-value = 0.024 (p ≤ 0.05).